Permanent Working Group on TVET in Kenya - Government of Kenya (Permanent Working Group on TVET in Kenya)
An engagement platform for public/private stakeholders to enhance the efforts of Kenya’s vocational training transformation
Library Catalog: tvetinkenya.net KerkoCite.ItemAlsoKnownAs: 2129771:GHBBWHEV 2317526:UWBRV7AH